Guadarrama González, Pablo. América Latina: marxismo y posmodernidad. Santa Clara, Cuba, y Bogotá,Colombia, Universidad de Las Villas y Universidad Incca de Colombia, 1994, 230 p. - Silnik, Gustavo David (1998)
Fil: Silnik, Gustavo David.